Crescimento vegetativo e acúmulo de nutrientes em frutos de cafeeiro conilon irrigado e não irrigado, na região atlântica da Bahia, Brasil - Covre, André Monzoli (2016)
Understanding the seasonal variations of the vegetative growth and the dynamics of formation of Conilon coffee fruits in non-irrigated crops and especially in irrigated conditions, relating them to the climatic conditions, it is an important tool, with direct implications for the management of the crop. The objective was to evaluate the vegetative growth of orthotropic and reproductive branches, the dry matter accumulation in fruits, leaves and branches of production, the concentration of nutrients in fruits and leaves, and the accumulation of nutrients in fruits of irrigated and non-irrigated coffee Conilon plants. The experiment was conducted for two years in the municipality of Itabela, Atlantic region of State Bahia, Brazil. Three-year-old Conilon coffee plants of the genotype 02 were used. A completely randomised splitplot experimental design was employed, with 14 replicates. The treatments consisted of irrigation and no irrigation of coffee plants in the plots, and subplots of different evaluation times (measurement of branches and fruit collecting and leaves). The growth rate of orthotropic and reproductive branches pending charge is higher in irrigated plants compared to non-irrigated. The maximum growth rates occur in the spring and minimum during graining and, or, during periods of drought, high temperature and low relative humidity. The growth rate of C. canephora branches is not limited by the average minimum air temperature. The dry matter accumulation curves and nutrients in irrigated Conilon coffee fruits and without irrigation were similar, adjusting to the sigmoidal model. The accumulation of dry matter in the fruit is higher in irrigated plants compared to non-irrigated. Nitrogen, potassium, calcium, iron and boron were the most nutrients found in fruits and Conilon coffee leaves in Bahia Atlantic region.